Microcirculatory and functional changes in the retina and visual channels in multiple sclerosis - E. P. Lantukh; M. V. Zueva; I. V. Tsapenko; O. V. Zaitseva; M. N. Zakharova; N. M. Maglakelidze; T. O. Simaniv (Российский офтальмологический журнал, 2018)
Purpose: to compare subtle changes in retinal and optic disk morphology and microcirculation and the functional activity of visual channels in patients with multiple sclerosis (MS) and optical neuritis (ON) in the medical history. Material and methods: 19 patients with remitting MS (duration of about four years) and ON developed about six months ago were tested by standard neurologic and ophthalmologic techniques, optical coherent tomography (OCT) with the angio OCT (RTVue XR 100 Avanti) protocol. The pattern ERG (PERG), as well as visual evoked potentials (VEP), on the reversing black/ white, pure luminance (black/yellow) and chromatic (red/green and blue/yellow) chess stimuli were recorded (RETI-port/ scan, Roland Consult, Germany). Results: At the level of superficial capillary plexus, the density and the area of vessels were reduced in the parafoveal zone, and the blood flow index dropped significantly (to 82.6% against the control). No statistically significant changes of blood flow were found in the peripapillary zone. The peak latency of P50 in the PERG responses to all stimuli showed a statistically significant reduction. The peak latency of N95 was delayed by an average of 10 % as compared to the controls. The amplitude of PERG N95 was moderately reduced for stimuli of all sizes. The elongation of the culmination time for the peak P100 was shown to be significant only in the VEP responses to blue/yellow patterns with angular sizes of 16° and 0.3°. A decrease in the thickness of the ganglion cells (GCC) complex correlated highly with reduced microcirculation in the superficial capillary plexus. Conclusion: Early changes of the retinal function were documented in patients with recent MS and ON history with almost equal involvement of the retinal ganglion cells of the parvo-, mango- and koniocellular systems into the pathological process. For the first time, we established direct correlation between the parameters of microcirculation and morphometry of the inner retina. Clinical significance of the simultaneous detection in MS patients of the delay of P100 latency in the VEP and reduction of the thickness of the SCC and the retinal nerve fiber layer was shown. For citations: Lantukh E.P., Zueva M.V., Tsapenko I.V., et al. Microcirculatory and functional changes in the retina and visual channels in multiple sclerosis. Russian ophthalmological journal. 2017; 10 (3): 29-41. doi: 10.21516/2072-0076-2017-10-3-29-41 (in Russian).